SURVEY OF INFORMATION TECHNOLOGY IN INDIAN PUBLICITY (International Journal of Engineering Sciences & Management Research, 2014)
Information Technology (IT) had a great impact in all aspects of life such as economy, businesses and enterprises. The globaleconomy is currently undergoing fundamental transformation in which IT plays a key role. IT has a real impact in most ofindustries and in all aspects of economy, while businesses and enterprises continue to undergo considerable changes. Usage ofthese technologies is revolutionizing the rules of business, resulting in structural transformation of enterprises. Modern businessesare not possible without help of information technology, which is having a significant impact on the operations of Small andMedium scale Business (SMB). It is claimed to be essential for the survival and growth of economies in general. SMB is drawingattention in developed and developing countries as well as in transition countries. It is generally recognized that SMB play a vitalrole in the revitalization and development of national economy in many countries and particular in the context of India. It isencouraging the development of SMB and the role that SMB sector can play in promoting economic and social development bycreating opportunities for employment. These components are described and discussed while more research and studies on theadoption of information technology in SMB in India are proposed as necessary